Gender Discourse’s Understanding and Knowledge of Family Planning Agent, Cadres, and Community Institutions towards Family Planning Promotion in Kediri Regency - Yuyun Agus Riani; Yun Fitrahyati Laturrakhmi (Metakom, 2018)
This data also supported by the results of the previous research which showed that the family planning always a woman as an object, controversy in social values, domination of decision making, power relations became several factors causing vasectomy and family planning for men was less adopted. From those descriptions, it is important for researchers to identify the understanding and knowledge of gender discourse in PLKB officers, KB cadres, and members of family planning institutions related to family planning promotion. This study uses an interpretative qualitative approach. While data collection conducted by using in-depth interviews and Focus Group Discussion (FGD). Key words : family planning promotion, gender discourse, understanding